Self-selection patterns among return migrants: Mexico 1990-2010 - Raymundo M. Campos-Vazquez; Jaime Lara (IZA Journal of Migration, 2012)
This paper analyzes the self-selection patterns among Mexican return migrants during the period 1990-2010. To calculate the selection patterns, we nonparametrically estimate the counterfactual wages that the return migrants would have experienced had they never migrated by using the wage structure of stayers. We find evidence that the selection patterns in observable skills change over time from positive selection in 1990 toward negative selection in 2010. Additionally, we observe that the wages of return migrants are larger than those that the migrants would have obtained had they not migrated.
Keywords: F22; J01; J61; O54; 330; Mexican migration; self-selection; return migration; wages